PENEGAKAN HUKUM TERHADAP PELAKU PENYALAHGUNAAN TEMBAKAU GORILA DI WILAYAH HUKUM KEPOLISIAN SULAWESI TENGAH - Tomuka, Maria Rose Marie; Jubair; Lestari, Titie Yustisia (JUSTITIABLE - Jurnal Hukum, 2026)
ABSTRACT The purpose of this study is to examine whether law enforcement has been carried out in accordance with statutory provisions and to identify the police strategies employed to address its circulation. The research employs a juridical-empirical method, utilizing a statutory and interview-based approach, supported by literature and official reports. The study was conducted at the Central Sulawesi Regional Police. The findings indicate that law enforcement against the abuse of gorilla tobacco, a synthetic narcotic substance, within the jurisdiction of the Central Sulawesi Regional Police has been implemented fairly well and in accordance with the prevailing laws and regulations, particularly Law Number 35 of 2009 on Narcotics and Minister of Health Regulation Number 30 of 2023. All procedural stages of the legal process from investigation, arrest, and seizure of evidence to laboratory testing have adhered to the established normative mechanisms. However, the implementation still faces technical challenges, such as the limited availability of synthetic substance detection tools and the lack of public participation in reporting cases of gorilla tobacco abuse. Moreover, the countermeasures undertaken by the Central Sulawesi Regional Police encompass both preventive efforts, including public awareness campaigns and cyber patrols, and repressive actions, such as arrests and prosecution of offenders. These strategies have proven to be relatively effective in reducing the incidence of abuse, though their effectiveness could be further enhanced through the optimization of cyber patrol operations and the strengthening of community participation in reporting narcotics-related offenses involving gorilla tobacco. Keyword: Law Enforcement; Gorilla Tobacco; Synthetic Narcotics; Central Sulawesi. ABSTRAK Tujuan penelitian ini adalah mengetahui penegakan hukum dilaksanakan sesuai ketentuan perundang-undangan serta strategi kepolisian dalam menanggulangi peredarannya. Metode penelitian yang digunakan adalah yuridis-empiris, dengan pendekatan undang-undang dan wawancara ditunjang literatur dan laporan resmi. Lokasi penelitian dilakukan di Kepolisian Daerah Sulawesi Tengah. Hasil penelitian menunjukkan bahwa penegakan hukum terhadap penyalahgunaan narkotika jenis tembakau gorila di wilayah hukum Kepolisian Daerah Sulawesi Tengah telah dilaksanakan dengan cukup baik dan sesuai dengan ketentuan peraturan perundang-undangan yang berlaku, khususnya Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika serta Peraturan Menteri Kesehatan Nomor 30 Tahun 2023. Seluruh tahapan proses hukum, mulai dari penyelidikan, penangkapan, penyitaan barang bukti, hingga pengujian laboratorium, telah mengikuti mekanisme yang diatur secara normatif. Meskipun demikian, pelaksanaannya masih menghadapi kendala teknis seperti keterbatasan alat deteksi zat sintetis dan minimnya partisipasi masyarakat dalam memberikan laporan terkait penyalahgunaan tembakau gorila. Selain itu, upaya penanggulangan yang dilakukan oleh Kepolisian Daerah Sulawesi Tengah telah mencakup langkah preventif melalui kegiatan sosialisasi dan patroli siber, serta langkah represif melalui operasi penangkapan dan proses hukum terhadap pelaku. Strategi tersebut dinilai cukup efektif dalam menekan angka penyalahgunaan, namun efektivitasnya masih perlu ditingkatkan melalui optimalisasi patroli siber dan peningkatan peran aktif masyarakat dalam pelaporan tindak penyalahgunaan narkotika jenis tembakau gorila.